2009
DOI: 10.1186/1471-2407-9-146
|View full text |Cite
|
Sign up to set email alerts
|

Safety and preliminary efficacy data of a novel Casein Kinase 2 (CK2) peptide inhibitor administered intralesionally at four dose levels in patients with cervical malignancies

Abstract: BackgroundCervical cancer is now considered the second leading cause of death among women worldwide, and its incidence has reached alarming levels, especially in developing countries. Similarly, high grade squamous intraepithelial lesion (HSIL), the precursor stage for cervical cancer, represents a growing health problem among younger women as the HSIL management regimes that have been developed are not fully effective. From the etiological point of view, the presence of Human Papillomavirus (HPV) has been dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 23 publications
0
61
0
Order By: Relevance
“…This is particularly relevant given the relative inefficacy of GSI treatment in T-ALL patients 14 and recent clinical data in patients with cervical cancer indicating that CK2 antagonists are well tolerated and may have antitumor efficacy. 15 Hence, we treated PTEN-positive T-ALL cell lines with GSI DAPT and/or the CK2-specific inhibitors DRB or TBB. Analyses of cell size (Figure 2A and Online Supplementary Figure S1), total cell counts ( Figure 2B and Online Supplementary Figure S2) and proliferation ( Figure 2C and Online Supplementary Figure S3) revealed that combination of GSI and CK2 inhibitors have a mild but consistent cooperative effect in diminishing leukemia proliferation.…”
mentioning
confidence: 99%
“…This is particularly relevant given the relative inefficacy of GSI treatment in T-ALL patients 14 and recent clinical data in patients with cervical cancer indicating that CK2 antagonists are well tolerated and may have antitumor efficacy. 15 Hence, we treated PTEN-positive T-ALL cell lines with GSI DAPT and/or the CK2-specific inhibitors DRB or TBB. Analyses of cell size (Figure 2A and Online Supplementary Figure S1), total cell counts ( Figure 2B and Online Supplementary Figure S2) and proliferation ( Figure 2C and Online Supplementary Figure S3) revealed that combination of GSI and CK2 inhibitors have a mild but consistent cooperative effect in diminishing leukemia proliferation.…”
mentioning
confidence: 99%
“…The antineoplastic effect of this peptide has been well documented in the preclinical setting in vitro and in vivo (13,17,18). In 2006, the peptide entered a phase I clinical trial on patients with HSILs, where safety and efficacy signs were registered (19). Moreover, in patients with stage 1B2/II cervical cancer, the MTD, biodistribution and modulation of a response biomarker were investigated following local administration of CIGB-300 (20).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, CIGB-300 exerts a broad antiproliferative effect on cell lines derived from breast, cervical, lung, colon and prostate cancer, while a robust antitumor effect was also observed in vivo in mouse models of cervical and lung cancer (13,17,18). In the clinical setting, CIGB-300 was investigated in a phase I clinical trial on high-grade squamous intraepithelial lesions (HSILs), establishing its safety and tolerability by local injection (19). More recently, another phase I clinical study on patients with stage 1B2/II cervical cancer allowed us to estimate the maximum tolerated dose (MTD) and the pharmacokinetics̸biodistribution profiles for CIGB-300 following local administration (20).…”
Section: Introductionmentioning
confidence: 99%
“…CIGB-300 elicits antitumor activity in different animal models when administrated by different routes [9]. As an investigational drug, CIGB-300 was previously tested in a First-in-Human trial where patients with high grade squamous intraepithelial lesion (HSIL) or epidermoid microinvasive cervical cancer received intralesional injections of this peptide-based drug [10]. That was the first clinical trial in which a drug was used to target the CK2 phosphoacceptor domain providing an early proof-of-principle of a possible clinical benefit.…”
Section: Additional Advantage Of the Cyclic Peptidesmentioning
confidence: 99%